Features of Legal Language and Its Translation Analysis in Indonesian-English “Settlement Termination Agreement” - Raskia Ella Muhaya; Raden Arief Nugroho (Yayasan Visi Intan Permata, 2024)
Translation procedures and translation quality assessment can be used to assist translators when translating to get more accurate results. This paper aims to find out what legal language features and procedures of translation are and determine the quality of the resulting translation. The data sources used are words, phrases, and sentences that contain legal linguistic features such as archaisms, technical terms, phrasal verbs, doublets, and word reciprocity. This research is a qualitative descriptive study and was compiled based on the translation procedure framework of 17 Newmark (1988) followed by an assessment of the quality of the translation by Nababan (2012). From the analysis, the most frequently used legal language features are technical terms and archaisms. Meanwhile, the most widely used procedure in settlement agreement documents is literal translation with a total of 18 data and a percentage of 23.3%. The second order is naturalization with a total of 15 and a percentage of 19.4%. These two procedures are most often used by translators in translating settlement agreement documents. The use of literal translation procedures dominates. This, of course, affects the quality of the translation of this document. Based on the evaluation of the quality of the translation carried out, the level of accuracy and acceptability is 89%, and the readability is 78%. So, it can be concluded that the results of the translation of this settlement termination agreement document can be declared valid because it is translated in accordance with the applicable legal system based on the target language.